Formation of Corporate Social Responsibility in the Agricultural Sector: Conceptual Approaches - Lunkina Tetiana I. (Problemi Ekonomiki, 2020)
In the modern world, economic relations that arise between business entities are increasingly influenced by social relations, which become dominant and determine the role and relevance of local social responsibility (LSR).The aim of the article is to explore conceptual approaches to formation of corporate social responsibility in the agrarian sector. The article analyzes the main modern conceptual approaches that influence formation of social responsibility. A conceptual model for forming social responsibility in the agrarian sector of the Ukrainian economy is created. It is established that forming social responsibility is possible provided that all levels of interaction are included. It is proved that the impact of social responsibility on the agrarian sector manifests itself through four levels of functioning. It is justified that each next level cannot be developed without the functioning of the previous one. The system of tools for enhancing local social responsibility by certain areas of an agrarian enterprise’s activities, in particular: technical, technological, economic, environmental and individual ones, is built. The list of agents of local social responsibility in the agrarian sector of the Ukrainian economy is supplemented, taking into account the criteria of the ISO standards. Based on the studies, it is found that the adoption of practices of local social responsibility in Ukraine is limited due to lack of information.